Main Edges of Mavjuda Hamidova's Literature Activity - Ahmadovich, Hayitov Shavkat; Farhodovna, Talibova Farida (Researchparks Publishing, 2023)
The article discusses the textual activity of the talented scientist Mavjuda Hamidova. Factors such as scientific theoretical aspects of the problem of the style of the textual scholar, the period that created it, creative environment, talent, skills were considered on the example of the work of the literary scholar Mavjuda Hamidova. The services of the textual scholar Hafiz Khorezmi, poet of the XIV century, and Mirzo Kulfat, a poet from Tashkent, were studied from the point of view of textual studies and published. The scientific and critical text of Alisher Navoi's works